Comparison of invasive versus noninvasive blood pressure measurements before and after hemorrhage in anesthetized greyhounds using the Surgivet V9203. (15th July 2013) - Drynan, Eleanor A.; Raisis, Anthea L.
Abstract Objective To determine the agreement between blood pressure obtained with a noninvasive technique and direct technique using the Surgivet V9203 at varying blood pressure levels created using a canine hemorrhage model. Design Experimental study. Setting University Teaching Hospital. Animals Twenty‐nine greyhounds with an average weight of 30 kg. Approval from the Murdoch University Animal Ethics Committee was obtained (R228609). Methods Arterial blood pressure (BP) was measured noninvasively (NIBP) via a cuff placed over the dorsal metatarsal artery and via a catheter in the contralateral dorsal metatarsal artery (IBP). Retrospectively the blood pressure measurements recorded were divided into various BP categories. A total of 84 paired readings were obtained. The data were further analyzed with respect to heart rate [<120/min and >120/min]. Comparison of the measurements was performed using the Bland–Altman method. Results For all categories, BP measurements were generally lower when recorded using the oscillometric technique [Systolic (Sys) bias 4.20 kPa (31.54 mm Hg), mean bias 0.52 kPa (3.93 mm Hg), and diastolic bias 1.04 kPa (7.83 mm Hg)]. Mean arterial BP had the least bias and greatest precision in the hypotensive group (bias 0.174 kPa (1.3063 mm Hg), precision 0.79 kPa (5.89 mm Hg)), low BP group (bias 0.62 kPa (4.67mm Hg) and precision 0.89 kPa (6.67mm Hg)) and normotensive group [bias 0.76 kPa (5.71 mm Hg) and precision 1.16 kPa (8.73 mmHg)]. Conclusions The results demonstrate that the agreement between NIBP measurements and IBP, are within the limits of agreement recommended by the American College of Veterinary Internal Medicine Hypertension Consensus Panel for all pressures except Sys BP. This suggests that mean and diastolic NIBP using the Surgivet V9203 are a clinically acceptable alternative of IBP in hypovolemic hypotensive dogs.